URARTIAN METALWORK DISCOVERED AT MURAT HÖYÜK, BINGÖL PROVINCE - Çavuşoğlu, Rafet; Özdemir, Abdulkadir; Özdemir, Ayşe (Peeters Publishers, 2021)
Rescue excavations in 2019 at Murat Höyük, Solhan district of modern Bingöl province,1 produced a large number of finds of Middle Iron Age date. These included a range of metal artefacts, some of which were grave gifts, that show the local impact of Urartian Period metalwork, and which constitute the subject of this study. The items we present here are of importance in terms of showing the effects of Urartian art and aesthetic understanding on metalwork in local settlements. © Nederlands Instituut voor het Nabije Oosten / Peeters. All rights reserved.